Simulation and Test of “Separated Burying Device” of Green Manure Returning Machine Based on the EDEM Software - Wang Yang; Jinfei Zhao; Xinying Liu; Linqiao Xi; Jiean Liao (Agriculture, 2022)
Today, China’s orchard area covers 11,874,850 ha. With China’s progress in implementing the strategy of “quality-based and environmental-friendly agricultural development”, green manure has been developed as a modernized green soil management method for use in orchard areas. Green manure shows the highest decomposition rate with a ploughing depth of 150 mm. To efficiently utilize green manure in orchard areas, a “separated burying device” was designed, which can realize “stalk falling and soil falling” simultaneously. The device was composed of rotary blades, an iron chain separation curtain, soil retaining board and compacting machine. The cooperation parameters of different parts of the proposed device were designed through a discrete element simulation test, and a cooperative parameter model of the proposed device was constructed. According to the simulation test, the highest coverage of the prototype (95.16%) was achieved only when the knife roller center of rotary tillage moved to the point where it had a horizontal distance of 378.76 mm from the root of the “iron chain separation curtain”, the width of the transverse soil retaining board was 187.78 mm and the included angle of the soil retaining board θ was 116.48°. Based on a model verification test, the burying rate was found to be 94.36%, which differed slightly from the simulation test results. The burying rate increased by 4.84% upon the application of a “separated burying device”. The “separated burying device” was able to increase the burying rate of green manure between rows in the orchard area. It is conducive to the full utilization of green manure resources and lays good sowing foundations for green manure resowing. The construction of a “separated burying device” and its cooperative parameter model can provide insight into the research, development and optimization of relevant machines, such as the stalk returning machine.